PELATIHAN PERSIAPAN KEGIATAN OLIMPIADE MATEMATIKA SEBAGAI TAMBAHAN EKSTRAKURIKULER DI SMAN 2 TANJUNG BALAI TAHUN PELAJARAN 2017/2018. - Anim Anim; Elfira Rahmadani; Yogo Dwi Prasetyo (STMIK Royal, 2019)
Abstract: Many ways taken by the government to realize the human resources of Indonesia with intellectual ability that can compete with the region even with other countries, one of them with a Mathematics Olympiad held both elementary / MI, SMP / MTs., SMA / SMK / MA even the level of Students . But sometimes those who can enjoy the Olympics are only certain schools. This is due to the lack of socialization conducted by the government regarding such activities as well as the factor of the school itself which still has a sense of inferior to compete with other schools. The purpose of this training activity is to improve the ability of students to solve Mathematics Olympic questions. The implementation of this activity was carried out at SMAN 2 Tanjung Balai, with the method of providing training and training strategies prepared by the writing team. the results of the training, that students are very enthusiastic in discussing Mathematical Olympiad problems with the tricks provided and they can easily answer the questions given without the constraints which means are expected to produce new seeds from the winners of the Mathematics Olympiad. Keywords: Training, Problem Prediction, Mathematics Olympiad. Abstrak: Banyak cara yang ditempuh oleh pemerintah untuk mewujudkan sumber daya manusia Indonesia dengan kemampuan intelektual yang dapat bersaing dengan daerah bahkan dengan Negara lain, salah satunya dengan diadakan Olimpiade Matematika baik tingkat SD/MI, SMP/MTs., SMA/SMK/MA bahkan tingkat Mahasiswa. Namun terkadang yang bisa menikmati kegiatan olimpiade tersebut hanyalah sekolah-sekolah tertentu saja. Hal tersebut disebabkan masih kurangmya sosialisasi yang dilakukan pemerintah mengenai kegiatan tersebut serta faktor dari sekolah itu sendiri yang masih memiliki rasa minder untuk bersaing dengan sekolah-sekolah lain. Tujuan dalam kegiatan pelatihan ini adalah untuk meningkatkan kemampuan peserta didik dalam menyelesaikan soal-soal Olimpiade Matematika. Penyelenggaraan kegiatan ini dilaksanakan di SMAN 2 Tanjung Balai, dengan metode memberikan pelatihan dan strategi pelatihan yang sudah disiapkan oleh tim penulis. hasil pelatihan tersebut, bahwa siswa sangat antusias dalam membahas soal-soal Olimpiade Matematika dengan trik yang diberikan dan mereka pun dapat dengan mudah menjawab soal-soal yang diberikan tanpa kendala yang berarti diharapkan mampu menghasilkan bibit-bibit baru dari pemenang Olimpiade Matematika. Kata Kunci : Pelatihan, Prediksi Soal, Olimpiade Matematika.